An Integrative Review of Fear of Childbirth - Kumiko Kido; Yuko Uemura (Journal of Midwifery, 2023)
This study aimed to provide knowledge for midwives to deepen their understanding of their clients when working closely with women during the perinatal period through an integrative review of â€˜fear of childbirthâ€™, and to clarify the research topics to be addressed in the future. Methods: This study used an integrative review (IR) method in addition to bibliometric analysis methods to classify and analyse the studies. Review questions (RQ) included 1. â€˜what is the status of research efforts (number of papers, location, etc.) on â€œfear of childbirthâ€?â€™, 2. â€˜what are the screening methods and prevalence of â€œfear of childbirthâ€?â€™, and 3. â€˜what can be learned from the findings of these studies?â€™Findings: RQ1: The number of papers published gradually increased after 1981 and has been increasing since 2000. Studies conducted in Scandinavia accounted for more than half of the total studies. Conversely, only five studies were conducted in Japan. RQ2: The Wijma Delivery Experience Questionnaire is a screening scale for fear of childbirth developed in Sweden, which has been translated and utilised in multiple languages. In meta-analyses worldwide, the prevalence of fear of childbirth has been reported to range from 3.7% to 43%. RQ3: Fear of childbirth leaves a negative impression of past childbirth experiences on womenâ€™s psychological well-being and subsequently leads to post-traumatic stress disorder. Intervention studies have shown that prenatal education can help couples overcome their fear of childbirth. However, the effectiveness of intervention studies that have examined these psychological aspects has not yet been clarified.Conclusion: The prevalence of fear of childbirth varies considerably, possibly owing to cultural differences. Research on fear of childbirth has reported negative effects on the postpartum period and on subsequent pregnancy and childbirth. Practising women-centred care may help prevent this fear.